Chan Gong’an and the “Flexible Method”: A Study on Xuedou Chongxian’s Classic Eulogies and Its Influence on Poetics - Rongrong Fu (Religions, 2023)
This paper argues that as poetics in the Song Dynasty developed, the thinking mode and methods of written expression in Chan Buddhism provided a theoretical reference and creative practical experience for the formation of poetic theories. This point is particularly evident in the formation of the “flexible method”, which was a key theory in poetics of the Song Dynasty. The theory comprises three layers of meaning: it advocates respecting forms, changing the meaning of those forms, and retaining the inherent grace of the forms through a natural and fluent syntax and rhetoric of “defamiliarization”. This theory was highly mature in the writing of Lv Benzhong of the Southern Song Dynasty. Xuedou Chongxian (980–1052), a sixth-generation Chan Buddhist at Xuedou Temple, made a vital contribution to its development, which is highlighted by studying the “Hundred Classic Eulogies”. Xuedou Chongxian initially constructed the connotation and system of the theory of the “flexible method” in both theoretical and practical aspects. His theory of poetics is rooted in the ways of thinking and cultivating of the Yunmen sect. He incorporated his dual identity as a senior monk of the Yunmen School and a poet. He inherited Guanxiu’s view of poetry and the Chan concept of Shitou Xiqian and Zhimen Guangzuo, which greatly impacted the literati of the Northern Song Dynasty and provided a conceptual basis for maturing and improving the “flexible method” theory. Therefore, Xuedou Chongxian’s value in the theoretical construction of the “flexible method” should not be ignored.